Distributed denial-of-service attack detection short review: issues, challenges, and recommendations - Ahasan Habib, AKM; Imtiaz, Ahmed; Tripura, Dhonita; Omar Faruk, Md.; Anwar Hossain, Md.; Ara, Iffat; Sarker, Sohag; Zainul Abadin, A F M (Bulletin of Electrical Engineering and Informatics, 2025)
An attacker can attack a network in several methods when there are a lot of device connections. Distributed denial-of-service (DDoS) attacks could result from this circumstance, which could damage resources and corrupt data. Therefore, irregularity in traffic data must be detected to identify malicious behavior in a network, which is critical for maintaining the integrity of current cyber-physical systems (CPS) as well as network security. This article attempts to study and compare various approaches to detecting DDoS attacks and expresses data paths for packet filtering for high-speed networks (HSN) performance, using machine or deep learning techniques used in intrusion detection systems (IDSs) and flow-based IDSs. The study presents a comprehensive DDoS attack taxonomy, categorizes detection strategies, and highlights the HSN accuracy assessment features. By exposing the problems and difficulties associated with DDoS attacks on HSN, several investigation paths are proposed to assist researchers in determining and developing the best solution.